2011
DOI: 10.1039/c0gc00931h
|View full text |Cite
|
Sign up to set email alerts
|

Rh(0) colloids supported on TiO2: a highly active and pertinent tandem in neat water for the hydrogenation of aromatics

Abstract: International audienceTiO2-supported Rh(0) nanoparticles were easily prepared in one step without calcination by a room temperature impregnation of the inorganic support with a prestabilized colloidal Rh(0) suspension. They are highly active and reusable catalysts for the hydrogenation of aromatics and chloroanisole derivatives in neat water with TOFs up to 33000 h−1. The comparison with the analogous silica system Rh@SiO2 was discussed showing higher catalytic selectivities and activities with Rh(0) colloids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…TEM analyses (Supporting Information) have showed that the well-dispersed preformed Ru particles possess sizes around 2.25 nm and from previous works, we could presume that similar sizes were obtained after heterogeneization on the inorganic support [25]. BET surface area has been measured by nitrogen physisorption.…”
Section: Catalysts' Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…TEM analyses (Supporting Information) have showed that the well-dispersed preformed Ru particles possess sizes around 2.25 nm and from previous works, we could presume that similar sizes were obtained after heterogeneization on the inorganic support [25]. BET surface area has been measured by nitrogen physisorption.…”
Section: Catalysts' Characterizationmentioning
confidence: 99%
“…Three different supports were used for the heterogeneization of Ru (0) The Ru(0) nanospecies were deposited on these various supports through a wet impregnation methodology, already reported in the literature [25,26,29]. First, 100 mL of an aqueous suspension of ruthenium NPs was prepared by reducing ruthenium chloride precursor (3.8 x 10 -4 mol RuCl 3 .…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…63 These nanocatalysts can be prepared by calcinations and are based on a room temperature impregnation of the inorganic support with the Rh-NPs. This is a relatively simple, environmentally friendly, and reproducible synthetic method compared to other methods.…”
Section: Hydrogenation Of Aromatic Compoundsmentioning
confidence: 99%